Scalable Synthesis of Ti3C2Tx MXene - Shuck, Christopher E.; Sarycheva, Asia; Anayee, Mark; Levitt, Ariana; Zhu, Yuanzhe; Uzun, Simge; Balitskiy, Vitaliy; Zahorodna, Veronika; Gogotsi, Oleksiy; Gogotsi, Yury (Advanced engineering materials, 2020)
Scaling the production of synthetic 2D materials to industrial quantities has faced significant challenges due to synthesis bottlenecks whereby few have been produced in large volumes. These challenges typically stem from bottom‐up approaches limiting the production to the substrate size or precursor availability for chemical synthesis and/or exfoliation. In contrast, MXenes, a large class of 2D transition metal carbides and/or nitrides, are produced via a top‐down synthesis approach. The selective wet etching process does not have similar synthesis constraints as some other 2D materials. The reaction occurs in the whole volume; therefore, the process can be readily scaled with reactor volume. Herein, the synthesis of 2D titanium carbide MXene (Ti3C2Tx) is studied in two batch sizes, 1 and 50 g, to determine if large‐volume synthesis affects the resultant structure or composition of MXene flakes. Characterization of the morphology and properties of the produced MXene using scanning electron microscopy, X‐ray diffraction, dynamic light scattering, Raman spectroscopy, X‐ray photoelectron spectroscopy, UV–visible spectroscopy, and conductivity measurements show that the materials produced in both batch sizes are essentially identical. This illustrates that MXenes experience no change in structure or properties when scaling synthesis, making them viable for further scale‐up and commercialization. Herein, a reactor used for MXene synthesis and the scalable production (50 g) of 2D Ti3C2Tx in one batch is demonstrated. The large‐scale Ti3C2Tx produced in this study has identical properties to conventional laboratory synthesis, implying that Ti3C2Tx and other MXenes can be produced in industrial quantities without a loss of properties.